Low Temperature Sintering and Characterization of MgO-B2O3-SiO2 Glass-Ceramics for LTCC Substrate Applications - Kumari P.; Tripathi P.; Parkash O.; Kumar D. (My University, 2025)
MgO-B2O3-SiO2 (MBS) glass-ceramics, with and without TiO2 as additive, has been prepared by sintering at 900oC and their structural, thermal and dielectric properties have been studied. The XRD and SEM studies show that the crystallization increases with addition of nucleating agent TiO2. The per cent thermal expansion decreases as TiO2 content increases. The value of dielectric constant increases with increasing wt% of TiO2 in MHz and GHz frequency range. The dielectric constant values lie in between 3 and 5 in the frequency range of 13.5–18 GHz and in between 9 and 11 at 1 MHz frequency. The microwave dielectric constants of the specimen have been found to be strongly dependent on TiO2 content. Due to low dielectric constant and low sintering temperature, this glass-ceramics is an attractive material for low temperature co-fired ceramics (LTCC) application. © 2017 The Indian Ceramic Society.